1999
DOI: 10.1207/s15324826an0601_6
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Cognitive Effects of Lyme Disease in Children

Abstract: Most studies of adults infected with Lyme disease (LD) have found adverse cognitive effects from the disease. In contrast, the only controlled study investigating cognitive effects of LD in a pediatric population found no effects after a 2-year follow-up. However, it was questioned whether the negative effects might take longer than 2 years to emerge. Therefore, this investigation reports a 4-year follow-up of the original sample. Twenty-five children with strictly defined LD were compared with 17 sibling cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
4

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 13 publications
1
19
0
4
Order By: Relevance
“…The appearance of post-Lyme disease symptoms seems to correlate with disseminated disease, a greater severity of illness at presentation, and delayed antibiotic therapy [12,[29][30][31][32][33]; but not with the duration of the initial antibiotic therapy [13,23]. Children appear to be less likely to develop post-Lyme disease symptoms [34][35][36][37][38][39][40][41][42].…”
Section: Post-lyme Disease Syndromementioning
confidence: 99%
“…The appearance of post-Lyme disease symptoms seems to correlate with disseminated disease, a greater severity of illness at presentation, and delayed antibiotic therapy [12,[29][30][31][32][33]; but not with the duration of the initial antibiotic therapy [13,23]. Children appear to be less likely to develop post-Lyme disease symptoms [34][35][36][37][38][39][40][41][42].…”
Section: Post-lyme Disease Syndromementioning
confidence: 99%
“…Arthralgias in joints previously affected by arthritis may persist for several months but usually do not restrict the physical or educational performance of adolescents. Late neurologic complications occurred in untreated children with Lyme arthritis (Szer et al, 1991) but have not been found after appropriate treatment (Adams et al, 1994). However, transient neurocognitive abnormalities have been described (Bloom et al, 1998).…”
Section: T a B L E 61 Diagnosis Of Lyme Arthritis In Children And Admentioning
confidence: 99%
“…Die Prognose von Kindern mit Erythema migrans oder früher Neuroborreliose ist exzellent, wenn die Erkrankung rasch mit den empfohlenen Antibiotika behandelt wird [69,76,77,78]. Sogar Kinder mit Lyme-Arthritis, die nicht antibiotisch behandelt wurden, zeigen eine Verminderung und ein Verschwinden der Symptome mit der Zeit [79].…”
Section: Krankheitsverlauf Und Prognoseunclassified
“…Arthralgien in vorher arthritischen Gelenken können über Monate persistieren, aber bei Kindern kommt es meist nicht zu einer Fibromyalgie. Späte neurologische Komplikationen sind bei nicht antibiotisch behandelten Kindern beschrieben [79], nicht aber nach angemessener antibiotischer Behandlung [81]. Vorübergehende neurokognitive Auffäl-ligkeiten sind hingegen beschrieben [82].…”
Section: Krankheitsverlauf Und Prognoseunclassified